2006
DOI: 10.4319/lo.2006.51.3.1410
|View full text |Cite
|
Sign up to set email alerts
|

Long-term temporal and spatial trends in phytoplankton biomass and class-level taxonomic composition in the hydrologically variable Neuse-Pamlico estuarine continuum, North Carolina, U.S.A.

Abstract: Phytoplankton diagnostic photopigments in near-surface waters (<0.5 m) were identified and quantified by high-performance liquid chromatography beginning in April 1994 in the Neuse River Estuary and in October 1999 in the Pamlico Sound, North Carolina. Photopigment concentrations were analyzed using ChemTax to determine the class-specific biomass of the dominant phytoplankton groups. Long-term annual and seasonal trends in phytoplankton biomass and composition were characterized along the river-estuarine conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 43 publications
4
48
0
Order By: Relevance
“…Picocyanobacteria and nanoflagellates usually dominate phytoplankton community biomass during the summer at mesohaline locations, accounting for >60% of the phytoplankton community biomass, followed by diatoms and dinoflagellates (Valdes-Weaver et al 2006;Paerl et al, unpublished size-fractionated HPLC data). The dominant N sources for the summer phytoplankton are ammonium and DON supplied by water column regeneration and diffusion out of sediments (Rizzo et al 1992;Twomey et al 2005).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Picocyanobacteria and nanoflagellates usually dominate phytoplankton community biomass during the summer at mesohaline locations, accounting for >60% of the phytoplankton community biomass, followed by diatoms and dinoflagellates (Valdes-Weaver et al 2006;Paerl et al, unpublished size-fractionated HPLC data). The dominant N sources for the summer phytoplankton are ammonium and DON supplied by water column regeneration and diffusion out of sediments (Rizzo et al 1992;Twomey et al 2005).…”
Section: Methodsmentioning
confidence: 96%
“…Biological and Chemical Measurements Chlorophyll a and diagnostic phytoplankton photopigments (chlorophylls and carotenoids) were determined using high-performance liquid chromatography (HPLC) coupled to an inline photodiode array spectrophotometer (Shimadzu SPD M10av; see Valdes-Weaver et al 2006 for complete details on sample processing). Photopigment concentrations were analyzed using the ChemTax matrix factorization program to determine the relative contribution of each of five phytoplankton taxonomic groups (chlorophytes, cryptophytes, cyanobacteria, diatoms, dinoflagellates) to total chlorophyll a (Mackey et al 1996).…”
Section: Storm Characteristicsmentioning
confidence: 99%
“…Water temperature (∌20°C) and the prevailing mesohaline conditions were conducive for K. veneficum growth (Nielsen 1996;Li et al 2000;Fensin 2004;Goshorn et al 2004). Prior studies have shown that algal blooms are common in the region of the estuary where this bloom developed (Valdes-Weaver et al 2006;Waggener 2006). One explanation is that the estuary widens in this region, increasing the residence time with respect to riverine discharge (Luettich et al 2000).…”
Section: Growth Phase Of the Bloommentioning
confidence: 98%
“…A study conducted across Brazil showed that the conditions in most of its inland water bodies ranged from mesotrophic to eutrophic (Abe et al, 2006) due to population and economic growth in their corresponding watersheds, which has compromised the quality of water supplies and of water for other uses, mainly due to the occurrence of cyanobacterial blooms (Sant'Anna et al, 2008). Despite its significance for predicting events and the identification of environmental changes, such as those related to climate, hydrology, eutrophication and oligotrophication (Barbosa and PadisĂĄk, 2004;Valdes-Weaver et al, 2006), long-term limnological studies in inland waters are scarce in Brazil (Seeliger et al, 2002).The aim of this study was to provide a longterm limnological characterisation of a subtropical shallow lake from southern Brazil (Guaiba Lake), in addition to verifying seasonal differences, including the influence of quali-quantitative phytoplankton variation. …”
mentioning
confidence: 99%